Effect of Maternal Education, Family Income, Mother-Midwife Interface, and the Incidence of Iron Deficiency Anemia in Pemalang, Central Java - Kurniati, Ade; Astirin, Okid Parama; Suryani, Nunuk (Journal of Maternal and Child Health, 2016)
Background: Maternal mortality rate was 359 per 100,000 live birth in Indonesia in 2012. An indirect cause of maternal mortality rate is anemia. This study aimed to investigate effect of maternal education, family income, mother-midwife interface, on the incidence of iron deficiency anemia in Pemalang, Central Java. ÃÂ Subjects and Method: This was an analytical observational with case control design. This study was conducted at Purwoharjo, Rowosari, and Petarukan health centers, Pemalang, Central Java. This study was carried out from March 2 to 27, 2016. A total of 146 pregnant women from the three health centers were selected for this study by fixed disease sampling. This study consisted of pregnant mothers with iron deficiency anemia (cases) and those without iron deficiency anemia (controls) with equal share. The dependent variable was iron deficiency anemia, which was measured by Sahli method. The independent variables were maternal education, family income, and mother-midwife interface. These variables were measured by a set of questionnaire. The data were analyzed by path analysis.Results: Better knowledge (b= -1.26; p=0.002), positive attitude (b= -1.01; p=0.019), stronger purchasing power (b= -1.16; p=0.004) had direct effects on reduced risk of iron deficiency anemia, and they were statistically significant. There were positive effects of higher income on stronger purchasing power (b=0.63; p=<0.001), mother-midwife interface on better knowledge (b=0.19; p=0.021), mother-midwife interface on positive attitude (b=0.21; p=0.023), and higher education on better knowledge (b=0.21; p=0.035).Conclusion: Better knowledge, positive attitude, stronger purchasing power, have direct effects on reduced risk of iron deficiency anemia. Higher income has indirect effect on reduced risk of iron deficiency anemia via stronger purchasing power. Mother-midwife interface has indirect effect on reduced risk of iron deficiency anemia either via better knowledge or positive attitude. It is suggested that pregnant mothers increase their interaction with midwives so that they are able to detect sign and symptom of anemia and to take necessary preventive action.Keywords: iron deficiency anemia, pregnant mother, mother-midwife interfaceCorrespondence :ÃÂ Ade Kurniati. Masters Program in Public Health, Sebelas Maret University, SurakartaJournal of Maternal of Child Health (2026), 1(4): 220-229https://doi.org/10.26911/thejmch.2016.01.04.03